2020
DOI: 10.1002/pen.25447
|View full text |Cite
|
Sign up to set email alerts
|

Review on nano‐and microfiller‐based polyamide 6 hybrid composite: Effect on mechanical properties and morphology

Abstract: Polyamide 6 (PA6)-based composites are of evolving interest due to its high strength, wear resistance, and barrier properties. The use of binary composites mostly with nanomaterial and glass fibers has been reviewed and presented in literature. However to obtain a balance of properties like stiffness, toughness, and strength along with cost reduction, ternary composites of PA6 have been designed. To achieve the balance, PA6 blend-based composites, with combination of microfiller/nanofiller or PA6 with combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 141 publications
1
27
0
Order By: Relevance
“…For aerogel [ 4 ] and chemical vapor deposition [ 5,6 ] approaches, the less single yield and poisonous gas make safety and environmental protection difficult. The mechanical approach [ 7,8,9 ] adopts continuous equipment, such as ultralengthy diameter‐ratio extruder [ 10,11 ] and microfoaming injection molding machine, [ 12–14 ] as well as reduces carbon agglomeration, thus satisfying commercial requirements.…”
Section: Introductionmentioning
confidence: 99%
“…For aerogel [ 4 ] and chemical vapor deposition [ 5,6 ] approaches, the less single yield and poisonous gas make safety and environmental protection difficult. The mechanical approach [ 7,8,9 ] adopts continuous equipment, such as ultralengthy diameter‐ratio extruder [ 10,11 ] and microfoaming injection molding machine, [ 12–14 ] as well as reduces carbon agglomeration, thus satisfying commercial requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Even though PA/rubber/rigid filler ternary composites have exhibited excellent toughness and strength at the same time, this strategy usually depends on filler dispersion and interfacial regulation significantly, which is typically required complex modification and difficult to control. [ 15 ] In addition, it has been demonstrated that in situ fibrillation technique is another way to improve the impact performance of polymer without sacrificing its stiffness. Kelnar et al.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber-reinforced polymers (FRP) exhibit unique material properties, specifically high stiffness-to-weight ratios and excellent corrosion resistance, compared to other materials, e.g., metals [ 1 , 2 , 3 ]. In some cases, combustible FRPs can replace non-combustible materials such as steel.…”
Section: Introductionmentioning
confidence: 99%